Factors affecting color stability of maxillofacial prosthetic silicone elastomer: A systematic review and meta-analysis. (October 2021) - Rashid, Farah; Barman, Aparna; Farook, Taseef Hasan; Jamayet, Nafij Bin; Yhaya, Mohd Firdaus Bin; Alam, Mohammad Khursheed
Purpose: This systematic review and meta-analysis explored the factors involved in the color stability and degradation of Maxillo-Facial Prosthetic Silicone Elastomer (MFPSE). Further exploration was done to analyze past literature discussing the potential benefits to color stability when nano-particles were combined with pigmented MFPSE. Method: The search for the articles was done according to PRISMA guidelines. Articles were searched from "Scopus" and "Web of Sciences" from the year 1970 to 2019. Searches were carried out by two reviewers until November 2019. Articles for systematic review were selected based on predefined eligibility criteria. Information regarding weathering conditions, pigments and filler-particle inclusion were extracted as appropriate. Further screening was done for meta-analyze case-control studies of red, blue and yellow pigments according to predefined scoring criteria. Meta-analysis was conducted on case-control studies that incorporated 5%, 10% and 15% TiO2 in MFPSE with the said pigments and was carried out using Cochrane Review Manager 5.3. Results: 30 studies were selected for systematic review and 6 studies were eligible for meta-analysis. The most prominent influencers of color stability were nano-fillers and the type of color used in the mixing. Furthermore, experimental conditions, weathering, color of investment plaster and the method of color detection all affected the degree of degradation. There was an overall significant difference found when TiO2 was incorporated with the pigmented silicone. There is significant difference when 10% ( P = 0.0004) TiO2 is incorporated with the red pigment, 5% ( P = 0.03) TiO2 with the yellow and 10% ( P < 0.0001) and 15% ( P = 0.02) TiO2 with the blue pigment. Conclusion: Type of pigment and nano-filler incorporated into the silicone play a role in influencing color stability. Incorporation of 10% TiO2 with red pigment, 5% with yellow pigment and 10% or 15% TiO2 with blue pigment provided some protection to the silicone elastomer from color degradation.